Challenges and strategies of needs assessment implementing in diabetes self-management education in Iran: A qualitative study - Fahimeh Kashani; Parvaneh Abazari; Fariba Haghani (Wolters Kluwer Medknow Publications, 2020)
Background: Many diabetes educators in Iran do not have the necessary skills and competence for performing a needs assessment, and thus, cannot provide Diabetes Self-Management Education (DSME) to suit individual educational needs and conditions. The purpose of the present study was to explore and analyze needs assessment implementation in DSME and evaluate the barriers and the appropriate strategies from educators' viewpoints. Materials and Methods: The present qualitative study was conducted using a conventional content analysis approach with semi-structured and in-depth interviews and using a purposeful sampling method on 20 nurses, physicians, and endocrinologists. The data of this study were collected from April to October 2018. The interviews were analyzed using the content analysis method of Graneheim and Lundman. Results: Qualitative data analysis resulted in the emergence of two main categories of educational challenges of needs assessment and managerial challenges of needs assessment and four subcategories (lack of structured educational planning, lack of needs assessment practical patterns, managers' insufficient support and supervision, and managers' insufficient attention to motivational factors). Conclusions: Educational strategic planning, managers' obligation and support in designing practical patterns, and supervision tools to evaluate educators' performance in the needs assessment domain can result in the promotion of DSME needs assessment, the efficiency of plans, and the promotion of society's health.